Strategies and Approaches in Teaching Values Education Among Public Secondary School In The Division Of Zambales - Edaño, Domingo C.; Meer, Christine Joy Q. (Future Science / FSH-PH Publications, 2021)
ABSTRACT The research aimed to look into the strategies and approaches in teaching values education among public secondary schools in the Division of Zambales, SY 2020-2021. The researcher used the quantitative descriptive-survey research design with questionnaire as the main instrument in gathering data from the population of three hundred (300) values educational teacher. The study revealed that the majority of Values Education teachers are female. The teachers always used Inculcation Approach as strategy in teaching Values Education. The respondents strongly agreed that the strategies in teaching Values Education was the most difficult dimension in teaching Values Education. There is significant differences on age and religious affiliation towards inculcation approach and significant on age towards Awareness Approach. No significant differences on moral reasoning approach, value clarification approach and evocation approach. Moreover, it was found that there is significant difference on age towards difficulty on contents while no significant differences on strategies and assessment respectively. There is negligible relationship between the academic performance and the strategies and approaches used in teaching values education. There is negligible relationship between the academic performance and the difficulties in teaching Values Education. The training design is hereby proposed entitled: Training Design in Values Education on Teaching Strategies and Approaches Amidst COVID 19-Pandemic. Based on the salient findings, the researcher recommended that head teachers and teachers in Values Education should make innovations on how Inculcation Approach in teaching the subject be more useful and effective; head teachers, principals, education specialist on Values Education of Division of Zambales may focus their In-service Trainings ways how teachers enhance the utilization and effectiveness of approaches; the teachers should look and utilize suitable techniques for Inculcation, Moral Reasoning, Awareness, Value Clarification and Evocation approaches; and head teachers and teachers are encouraged to attend national and international trainings and seminars for better understanding and improved skill in selecting appropriate strategies, on the development of learning content and assessment procedures in Values Education.